2012
DOI: 10.1016/j.ridd.2012.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental problems in maltreated children referred with indiscriminate friendliness

Abstract: We aimed to explore the extent of neurodevelopmental difficulties in severely maltreated adopted children. We recruited 34 adopted children, referred with symptoms of indiscriminate friendliness and a history of severe maltreatment in their early childhood and 32 typically developing comparison children without such a history, living in biological families. All 66 children, aged 5-12 years, underwent a detailed neuropsychiatric assessment.The overwhelming majority of the adopted/indiscriminately friendly group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 19 publications
3
52
1
Order By: Relevance
“…The Disinhibited subtype is characterised by indiscriminate friendliness which can be persistent and it has been suggested that this may be associated with personality problems in adult life (Lyons-Ruth, 2008). We have previously shown that children with indiscriminate friendliness can have complex neurodevelopmental problems and yet are frequently not engaged with therapeutic services (Kocovska et al, 2012). Sufferers can have problems with emotional and behavioural functioning and affect regulation ( Zeanah et al, 2002;Green 2003;Rutter and Sonuga-Barke, 2010;Gleason et al, 2011), and research with international (mainly post-intitutionalised) adoptees has demonstrated an association between indiscriminate friendliness and abnormalities of the Hypothalamo-Pituitary-Adrenal (HPA) axis, which governs the secretion of stress hormones such as cortisol .…”
Section: Introductionmentioning
confidence: 99%
“…The Disinhibited subtype is characterised by indiscriminate friendliness which can be persistent and it has been suggested that this may be associated with personality problems in adult life (Lyons-Ruth, 2008). We have previously shown that children with indiscriminate friendliness can have complex neurodevelopmental problems and yet are frequently not engaged with therapeutic services (Kocovska et al, 2012). Sufferers can have problems with emotional and behavioural functioning and affect regulation ( Zeanah et al, 2002;Green 2003;Rutter and Sonuga-Barke, 2010;Gleason et al, 2011), and research with international (mainly post-intitutionalised) adoptees has demonstrated an association between indiscriminate friendliness and abnormalities of the Hypothalamo-Pituitary-Adrenal (HPA) axis, which governs the secretion of stress hormones such as cortisol .…”
Section: Introductionmentioning
confidence: 99%
“…Neurodevelopmental research shows that school-aged adopted children with a history of severe maltreatment can have very complex and sometimes disabling neuropsychiatric problems and/ or language delay, but there has been no study of association between both types of disorders. 36 The process whereby language regulates behavior begins during childhood: children use speech to plan tasks, regulate their emotions, and guide their thoughts. Due to deficits in any of these speech-influenced developmental activities, children with CD may have difficulty dealing with stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical group: All clinical children were recruited from a pool of participants from a previous research study regarding neurodevelopmental difficulties in maltreated children with indiscriminate friendliness (Kocovska et al, 2012). All participating children had experienced severe maltreatment in the early years, prior to being adopted (age of adoption range 16 months to 7 years), including emotional and/or physical neglect and/or physical abuse often in the context of parental mental illness and/or drug and alcohol problems.…”
Section: Methodsmentioning
confidence: 99%
“…All participating children had experienced severe maltreatment in the early years, prior to being adopted (age of adoption range 16 months to 7 years), including emotional and/or physical neglect and/or physical abuse often in the context of parental mental illness and/or drug and alcohol problems. In 7 addition, all participating children had indiscriminate friendliness as measured by standardised instruments (for detail regarding the sampling, please see (Kocovska et al, 2012) and had cognitive functioning in the normal range.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation